2012
DOI: 10.1371/journal.pone.0041417
|View full text |Cite
|
Sign up to set email alerts
|

Arginine-Specific Mono ADP-Ribosylation In Vitro of Antimicrobial Peptides by ADP-Ribosylating Toxins

Abstract: Among the several toxins used by pathogenic bacteria to target eukaryotic host cells, proteins that exert ADP-ribosylation activity represent a large and studied family of dangerous and potentially lethal toxins. These proteins alter cell physiology catalyzing the transfer of the ADP-ribose unit from NAD to cellular proteins involved in key metabolic pathways. In the present study, we tested the capability of four of these toxins, to ADP-ribosylate α- and β- defensins. Cholera toxin (CT) from Vibrio cholerae a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Defensins also inhibit diverse enzymatic toxins, such as the binary anthrax lethal toxin (Kim et al, 2005), Corynebacterium diphtheriae diphtheria toxin (Kim et al, 2006), Pseudomonas aeruginosa exotoxin A (Kim et al, 2006), Clostridium difficile toxin B [TcdB; (Giesemann et al, 2008)], Staphylococcus aureus staphylokinase (Bokarewa and Tarkowski, 2004), and others (Castagnini et al, 2012; Hooven et al, 2012). Notably, bacterial toxins represent a variety of enzymatic and structural classes of proteins and therefore cannot be selected by defensins based solely on their specific activity or structure.…”
Section: Introductionmentioning
confidence: 99%
“…Defensins also inhibit diverse enzymatic toxins, such as the binary anthrax lethal toxin (Kim et al, 2005), Corynebacterium diphtheriae diphtheria toxin (Kim et al, 2006), Pseudomonas aeruginosa exotoxin A (Kim et al, 2006), Clostridium difficile toxin B [TcdB; (Giesemann et al, 2008)], Staphylococcus aureus staphylokinase (Bokarewa and Tarkowski, 2004), and others (Castagnini et al, 2012; Hooven et al, 2012). Notably, bacterial toxins represent a variety of enzymatic and structural classes of proteins and therefore cannot be selected by defensins based solely on their specific activity or structure.…”
Section: Introductionmentioning
confidence: 99%
“…The list of bacterial ARTs inhibited by defensins extends to NarE, ADP-ribosylating toxins from Neisseria meningitidis (mNarE toxin; (Castagnini et al, 2012)) and N. gonorrhoeae (gNarE toxin; (Rodas et al, 2016)), while cholera toxin (CT) and pertussis toxin (PT) were not affected by the peptides, implying that properties unrelated to the specific catalytic activity of the toxins were targeted by the defensins.…”
Section: Defensin-susceptible Bacterial Toxins/effector Proteinsmentioning
confidence: 99%
“…To assess whether bacterial ARTs, might employ similar mechanisms of defensin inactivation, P. aeruginosa exoenzyme S (ExoS), as well as CT, PT, DT, and ETA were examined but found to be unable to ADP-ribosylate HNP1 (Kim et al, 2006; Paone et al, 2002). In partial contradiction, more sensitive detection techniques revealed that CT and another bacterial ART toxin, Escherichia coli heat labile enterotoxin (LT) can ADP-ribosylate HNP1 and hBD1 in vitro (Castagnini et al, 2012). Given that only a small fraction of defensins was modified under ideal experimental conditions in vitro (Castagnini et al, 2012), the in vivo relevance of this modification by bacterial ART toxins is uncertain.…”
Section: Defensin-susceptible Bacterial Toxins/effector Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arginine-specific mono ADP-ribosylation in vitro of antimicrobial peptides by ADPribosylating toxins (Castagnini et al, 2012) Interleukin-5 receptor TOF Mutation of N-glycosylation sites to determine effect on function (Ishino et al, 2011) Interleukin-11 TOF (sinapinic), glycoprotein Introduction of O-glycans in the non-core region to investigate function (Yanaka et al, 2011) Lipoproteins…”
Section: Abbreviationsmentioning
confidence: 99%